Neutrophil-lymphocyte ratio as a valuable prognostic marker in idiopathic sudden sensorineural hearing loss - Kang, Jeong Wook; Kim, Myung Gu; Kim, Sung Su; Im, Heh-In; Dong, Sung Hwa; Kim, Sang Hoon; Yeo, Seung Geun (Acta oto-laryngologica, 2020)
Background: Neutrophil-to-lymphocyte ratio (NLR) has emerged as a marker for degree of inflammation. Inflammation has been regarded as one of the causes of idiopathic sudden sensorineural hearing loss. Objectives: This study investigated the potential association between neutrophil-to-lymphocyte ratio (NLR) and prognosis in patients with idiopathic sudden sensorineural hearing loss (ISSNHL). Material and methods: This retrospective, case-control clinical trial analyzed data from 186 subjects diagnosed with ISSNHL and admitted to Kyung-Hee Medical Center between March 2016 and February 2019. Hematologic and audiometric parameters were measured. Results: NLR showed a linear correlation with hearing recovery in patients with ISSNHL, with hearing gain (dB) = 56.698 - 3.718 × NLR (r 2 = 0.451, p = .001). Hearing recovery at all frequencies was numerically higher in patients with low (<6.661) than higher (≥6.661) NLR at all frequencies and was significantly higher at 500, 1000, 2000, 3000, and 4000 Hz. Hearing thresholds at 250, 500, 1000, 2000, 3000, and 4000 Hz in the low NLR group were significantly lower after treatment. Conclusions and significance: The ability to recover from ISSNHL decreases as NLR increases. NLR may be a valuable prognostic marker in patients with ISSNHL.